Malaria and associated factors among under-five children in Borena pastoral communities, southern Ethiopia - Aliyo, Alqeer; Golicha, Wako; Fikrie, Anteneh (Frontiers in Parasitology, 2024)
Background: Malaria continues to be an important threat to public health and infects millions of children under-five years of age each year. Despite Ethiopia has set targets for at-risk group interventions to eradicate and manage malaria, the illness is still a serious public health problem in areas where it is endemic, especially in the Borena zone's unique lowlands.Objective: This study aimed to determine the prevalence of malaria and associated factors among children in Borena pastoral communities, the Oromia regional state, southern Ethiopia, in 2022.A community-based cross-sectional study was used from March 1 st to April 30, 2022, among 437 randomly selected households with under-five years children in pastoral communities in the Borena zone. Data were collected through face-to-face interviews with structured and pretested questionnaires and blood sample examination using microscopy. Thick and thin blood smears were prepared and examined under a microscope at the health centre to confirm malaria cases. The data were analyzed using SPSS version 25. Bivariate and multivariable logistic regression analyses were used to identify factors associated with malaria, and a p-value < 0.05 was used to declare statistical significance.The prevalence of malaria among children under-five years of age was 27.8% (95% CI = 23.5-32.1), and the prevalence of P. falciparum, P. vivax, and mixed malaria were 68.4%, 25.6%, and 6%, respectively. Regarding the proportion of malaria among age groups, 81% of children under-five years of age between 48 and 59 months were malaria-positive. In this study, fever within the last week [AOR=13.34, 95% CI =6.37-27.95], and not sleeping under insecticidetreated nets (ITNs) [AOR=3.10, 95% CI =1.95-4.92] were significantly associated with malaria.The age of the children was negatively associated with malaria prevalence.The prevalence of malaria among children under 5 years old was high during the rainy season in this pastoral region of Ethiopia. Factors such as fever in the last week and not sleeping in insecticide-treated nets were significantly associated with malaria. Therefore, to reduce malaria-related infections and deaths among children under-five years of age, the government should increase the availability and utilization.